The role of genetic variation in TCF7L2 and KCNJ11, dietary intake, and physical activity on fasting plasma glucagon-like peptide-1 in male adolescents - Harry Freitag Luglio; Emy Huriyati (Paediatrica Indonesiana, 2017)
Background Transcription factor 7-like 2 (TCF7L2) and potassium voltage-gated channel subfamily j member 11 (KCNJ11) gene polymorphisms have been associated with type 2 diabetes mellitus (T2DM) via regulation of insulin production. Ingested nutrients induce glucagon-like peptide-1 (GLP-1), which in turn induces insulin secretion.Objective To evaluate the relationship between TCF7L2 and KCNJ11 gene polymorphism, dietary intake, and physical activity on fasting plasma GLP-1 in normal male adolescents.Methods This observational study with a cross-sectional design included 54 male adolescents selected from high schools in Yogyakarta, Indonesia. Interviews were done to collect data on energy intake and physical activity. The GLP-1 and insulin levels were measured from fasting blood plasma. The TCF7L2 and KCNJ11 gene polymorphisms were analyzed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP).Results Fasting GLP-1 was positively correlated with energy intake (r=0.276; P=0.047), but not with physical activity (r=0.011; P=0.936). The GLP-1 concentration was not associated with TCF7L2 and KCNJ11 gene polymorphisms (all P>0.05). In subjects with an EE genotype (KCNJ11), GLP-1 was not correlated with insulin (r=-0.036; P=0.435). However, in subjects with an EK genotype (KCNJ11), GLP-1 was positively correlated with insulin (r=0.394; P=0.026).Conclusion GLP-1 concentration is positively correlated with body weight. Among male adolescents with a genetic variation in KCNJ11 (EK genotype), there is a significant correlation between GLP-1 and insulin signalling.